2017
DOI: 10.1103/physrevd.96.032002
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the top quark mass in the dileptonic tt¯ decay channel using the mass observables Mb

Abstract: Measurement of the top quark mass in the dileptonic tt decay channel using the mass observables M b , M T2 , and M b ν in pp collisions at √ s = 8 TeVThe CMS Collaboration * AbstractA measurement of the top quark mass (M t ) in the dileptonic tt decay channel is performed using data from proton-proton collisions at a center-of-mass energy of 8 TeV. The data was recorded by the CMS experiment at the LHC and corresponds to an integrated luminosity of 19.7 ± 0.5 fb −1 . Events are selected with two oppositely cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…In Ref. [31] the sensitivity of m MC t determinations from exclusive hadronic variables such as the B-meson energy E B [32], the B-lepton invariant mass m B [33] or the transverse mass variables m T 2 [34][35][36][37] to variations of the parameters of the MC hadronization models in PYTHIA 8 and Herwig 6 was studied. They found that for top mass determinations based on these distributions to be competitive with direct reconstruction methods these hadronization parameters would have to be constrained significantly more precisely than what is possible from usual multi-purpose tuning.…”
Section: Prelude and Reviewmentioning
confidence: 99%
“…In Ref. [31] the sensitivity of m MC t determinations from exclusive hadronic variables such as the B-meson energy E B [32], the B-lepton invariant mass m B [33] or the transverse mass variables m T 2 [34][35][36][37] to variations of the parameters of the MC hadronization models in PYTHIA 8 and Herwig 6 was studied. They found that for top mass determinations based on these distributions to be competitive with direct reconstruction methods these hadronization parameters would have to be constrained significantly more precisely than what is possible from usual multi-purpose tuning.…”
Section: Prelude and Reviewmentioning
confidence: 99%
“…• This event topology is realized in the SM production of tt events, providing a useful toy playground for testing new ideas for studying new physics [57][58][59][60].…”
Section: Dilepton Tt Kinematics and Mass-constraining Variablesmentioning
confidence: 99%
“…[35], the use of lowest Mellin moments of lepton kinematic distributions is discussed. In the leptonic channel, it is also possible to use distributions based on the "stransverse" mass variable [36], which generalizes the concept of transverse mass for a system with two identical decay branches [37,38].…”
Section: Introductionmentioning
confidence: 99%